Pengaruh Kompetensi, Pengalaman, Dan Etika Profesi Auditor Terhadap Kualitas Audit Pada KAP Di Surabaya - Adinda Meriayusti; Anik Yuliati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of competence, experience, and professional ethics of auditors on audit quality at KAP in Surabaya. The population specified in this study are auditors who are domiciled as working partners at KAP in Surabaya and are registered in the IAPI Directory in 2022. Determining the number of samples was obtained using the slovin formula, resulting in a total of 102 auditors as respondents. The method for sampling is probability sampling with simple random sampling method. This type of research is quantitative research with the Partial Least Square (PLS) analysis technique using SmartPLS version 4.0 software. The results of this study indicate that (1) Competence has a positive and significant effect on audit quality, it can be seen from the regression coefficient value of 0,082 and the p-value <0,05, so H1 is accepted. (2) Experience has a positive and significant effect on audit quality, which can be seen from the regression coefficient of 1,007 and the p-value <0,05, so H2 is accepted. (3) Professional Ethics has a negative and significant effect on audit quality, it can be seen from the regression coefficient -0,117 and the p-value <0,05, so H3 is accepted. Keywords: Competence, Experience, Professional Ethics, Audit Quality